Contemporary Forms of Family and School Collaboration in the Process of Preparing Children for Starting School - Parlić Božović, Jasna Lj.; Stoiljković, Ivana K. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Taking into account the modern living conditions characterized by an accelerated rate of life and work, the rapid development and progress of science and technology, the role of families in preparing children for school is becoming increasingly important. The collaboration between the family and the school is also necessary because of the expectations that the society has from the educational systems to enable the child with the emotional stability and undisturbed growth and progression, and to make sure that the child accepts the transition to primary school in the best possible way. This type of collaboration is also necessary because it is one of the conditions for the manifestation of the positive effects of the upbringing and the educational process. Realization of the education and upbringing work, apart from the continuous collaboration, also implies attentiveness of the parents for some of the particular and individual ways of collaboration. It is on these assumptions that the very outcome of the collaboration between the families and the school depends. The methods and domains of the family influence are abundant and diverse and they depend upon the characteristics of the wider social community in which the child is growing up, as well as the readiness of the parents, which shall be described in this work. The success of the Home-School Collaboration greatly depends upon the teacher’s personality and the way in which the teacher communicates with the parents, as well as the teacher’s readiness to meet the needs of the parents whose child is starting school. The communication channels must always be open, otherwise, the efforts might become ineffective. These assumptions will be examined theoretically and empirically in this work.